Caribbean Report 24-03-1997 - Forrester, Gilroy (interviewee); Forrester, Violet (interviewee); Grant, Bernie (interviewee); Rowe, Yvette (anchor); Hayes, Rosie (correspondent); Smith, Clifford (correspondent); Bryan, Anthony (interviewee); Jean, Wyclef (interviewee); Rushe, George (correspondent) (The British Broadcasting Corporation, 1997)
In Britain a seven year old girl is soon to be separated from her father and sent to a children’s home in Jamaica. Next, a diplomatic row is brewing between Cuba and the United States over the opening of a pouch. It is claimed that the pouch was carrying subversive material and therefore violated Cuban laws. In the following, the European Union has approved the conclusion of an agreement with the United Sates for the dismantling of tariffs on alcoholic spirits including rum. However, the US agreement would not affect the access which ACP rum has to the European market under the Lome Convention. In the following, there has been unrest in Haiti for the past month. Haiti has literally become a battle ground as demonstrators have been protesting privatisation reforms as well as slum conditions in the country. Next, still in Haiti, the United States based band the Fugees is staging a charity concert in an attempt to promote peace there. In the final segment, Bermuda’s Environment Minister, will become premier tomorrow. She would be the first female premier in Bermuda.
1. Headlines (00:00-15:27)
2. The plight of a seven year old school girl faced with being sent to live in a Jamaican orphanage. The relatives of the seven year old school girl and British Member of Parliament, Bernie Grant are interviewed (00:28-04:03)
3. A diplomatic row in Havana over the opening of a pouch sent from the United States. Rosie Hayes reports (04:04-06:01)
4. The dismantling of tariffs on rum as a prelude in Brussels. Clifford Smith reports (06:02-08:14)
Keywords: Forrester, Whitney.; Diplomatic pouch.; Council of Ministers Meeting -- Brussels.; Tariffs -- Rum.; European Union.; Demonstrations -- Haiti.; Fugees.; Jean, Wyclef.; Gordon, Pamela.